EVALUASI REVOLUSI INDUSTRI 4.0 PADA BIDANG PERTANIAN MENGGUNAKAN MODEL INTEGRASI DELONE AND MCLEAN, UTAUT DAN HOT FIT. - Pujo Hari Saputro; Arbiati Faizah; Reza Augusta J.F (Teknik Informatika, 2020)
This study tries to evaluate the industrial revolution 4.0 implementation results in agriculture in form of oyster mushroom temperature management technology. This implementation is intended to improve the quality and quantity of mushroom harvests, however further evaluation is still needed to determine the success and acceptance of the community towards the proposed technology. Evaluations were carried out using the integration of the DeLone and Mclean Success Models, the UTAUT acceptance model coupled with the Hot FIT model. The three models are then integrated to form a new model that is used to construct the questionnaire as an assessment. From the results of the 7-steps fit model, it can be concluded that the proposed model can be used and suitable for this study. From the results of the path analysis test it was concluded that human and technological factors will positively influence the use of the technology implemented. Lastly, as long as the proposed technology is used by mushroom farmers, it can be categorized as successful or successful..